Prostatic Arterial Supply: Anatomic and Imaging Findings Relevant for Selective Arterial Embolization - Bilhim, T (2012)
PURPOSE: To describe the anatomy and imaging findings of the prostatic arteries (PAs) on multirow-detector pelvic computed tomographic (CT) angiography and digital subtraction angiography (DSA) before embolization for symptomatic benign prostatic hyperplasia (BPH). MATERIALS AND METHODS: In a retrospective study from May 2010 to June 2011, 75 men (150 pelvic sides) underwent pelvic CT angiography and selective pelvic DSA before PA embolization for BPH. Each pelvic side was evaluated regarding the number of independent PAs and their origin, trajectory, termination, and anastomoses with adjacent arteries. RESULTS: A total of 57% of pelvic sides (n = 86) had only one PA, and 43% (n = 64) had two independent PAs identified (mean PA diameter, 1.6 mm ± 0.3). PAs originated from the internal pudendal artery in 34.1% of pelvic sides (n = 73), from a common trunk with the superior vesical artery in 20.1% (n = 43), from the anterior common gluteal-pudendal trunk in 17.8% (n = 38), from the obturator artery in 12.6% (n = 27), and from a common trunk with rectal branches in 8.4% (n = 18). In 57% of pelvic sides (n = 86), anastomoses to adjacent arteries were documented. There were 30 pelvic sides (20%) with accessory pudendal arteries in close relationship with the PAs. No correlations were found between PA diameter and patient age, prostate volume, or prostate-specific antigen values on multivariate analysis with logistic regression. CONCLUSIONS: PAs have highly variable origins between the left and right sides and between patients, and most frequently arise from the internal pudendal artery.